Outcomes of direct superior approach and posterolateral approach for hemiarthroplasty in the treatment of elderly patients with displaced femoral neck fractures: A comparative study - Hu, Wei; Xu, Wen-Bo; Li, Hao; Jiang, Wen-Hua; Shao, Yin-Chu; Shan, Ji-Chun; Yang, Di; Wan, De-En; Shuang, Feng (Frontiers in Surgery, 2023)
Hemiarthroplasty is a surgical choice for super-aged patients with a high surgical risk and a sedentary lifestyle. The direct superior approach (DSA), a minimally invasive modification of the posterior approach, is rarely studied in hemiarthroplasty. The aim of the present study was to compare the clinical outcomes in elderly patients with displaced femoral neck fractures undergoing hemiarthroplasty via DSA with the conventional posterolateral approach (PLA). A total of 48 elderly patients with displaced femoral neck fractures who underwent hemiarthroplasty between February 2020 and March 2021 were retrospectively included in the study. Of them, 24 patients (mean age 84.54 ± 2.11 years) were treated with hemiarthroplasty via DSA (DSA group), while the other 24 patients (mean age 84.92 ± 2.15 years) were treated with hemiarthroplasty via PLA (PLA group). Clinical outcomes, perioperative data, and complications were recorded. There were no obvious differences in the baseline characteristics between the DSA and PLA groups, including age, gender, body mass index, Garden type, American Society of Anesthesiologists score, and hematocrit. Perioperative data showed that the length of the incision in the DSA group was smaller than that in the PLA group (p < 0.001). However, the duration of the operation and blood loss in the DSA group were longer and higher than those in the PLA group, respectively (p < 0.001). In addition, the DSA group had a shorter hospitalization time than the PLA group (p < 0.001). The visual analog scale score and Harris score 1 month postoperatively in the DSA group were better than those in the PLA group (p < 0.001). Moreover, there were no significant differences between the two groups in Harris score (for assessment dysfunction) 6 months postoperatively (p > 0.05). DSA is less invasive and has better clinical outcomes, which can allow an early return to daily living activities in elderly patients with displaced femoral neck fractures undergoing hemiarthroplasty.